URGENSI TENTANG PERATURAN SURROGACY (SEWA RAHIM) DI INDONESIA - Arifin, Husnul; Gultom, Elfrida Ratnawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
A wife who has experienced uterine cancer which resulted in her uterus being removed so that it is no longer possible to have genetic children from the ovum and sperm of a legitimate married couple, while children are one of the gifts that give happiness to married couples, through the In Vitro Fertilization (IVF) Program generally used by married couples who find it difficult to have children, namely the wife has difficulty getting pregnant so she cannot raise the fetus in her own womb, surrogacy has not yet been legalized by regulation, this research uses a legal approach and supporting books which is what this paper aims to do. provides a solution for married couples who do not have a uterus to have children through surrogacy.